Structural, dielectric, ferroelectric and electrical properties of lead-free Ba0.9Sr0.1Ti0.9Sn0.1O3 ceramic prepared by sol–gel method. (2022) - Khardazi, S.; Zaitouni, H.; Asbani, B.; Mezzane, D.; Amjoud, M.; Choukri, E.; Terenchuk, S.; Erramli, A.; Gagou, Y.
Abstract: Lead-free Ba0.9 Sr0.1 Ti0.9 Sn0.1 O3 (BSTSn) ceramic was prepared by the sol–gel method. X-ray diffraction measurement at room temperature reveals the single-phase formation with tetragonal structure refined in the P4mm space group. Raman spectroscopy analysis at room temperature was used to confirm the structure of BSTSn ceramic sintered at 1420 °C during 5 h. The dielectric measurements were examined in the temperature range [−90 – 250 °C] and the frequency range of [100 Hz – 1 MHz]. The maximum dielectric constant was found to be ∼ 5484 (1 kHz) at room temperature. The diffuse phase transition characteristic at 1 kHz was ascribed by the modified Curie-Weiss law. Macroscopic polarization – field (P – E) hysteresis loops recorded at room temperature (RT) confirm the ferroelectric nature of BSTSn ceramic. Impedance spectroscopy analysis of BSTSn sample in the temperature range 300–380 °C reveals the presence of two relaxation contributions originated from grains and grain boundaries. Activation energies of grain and grain boundaries resistances were deduced in order to determine the conduction mechanism of the studied sample.